Nd3+ doped Gd3Sc2Al3O12 nanoparticles: towards efficient nanoprobes for temperature sensing. Issue 21 (16th May 2019) - Dantelle, Geraldine; Matulionyte, Marija; Testemale, Denis; Cantarano, Alexandra; Ibanez, Alain; Vetrone, Fiorenzo
Abstract : Higher synthesis temperature of GSAG:Nd 3+ nanocrystals results in enhanced relative thermal sensitivity ( S r ) as well as coherence length ( L c ). Abstract : Development of contactless temperature-probing nanoplatforms based on thermosensitive near-infrared (NIR) light-emitting nanoparticles opens up new horizons for biomedical theranostics at a deep tissue level. Here, we report on the crystallinity and relative thermal sensitivity of NIR emitting Nd 3+ doped Gd3 Sc2 Al3 O12 (GSAG:Nd 3+ ) nanoparticles synthesized by a solvothermal method. The obtained nanoparticles are well-crystallized, with sizes less than 100 nm, and can be dispersed in water without any additional functionalization. Upon excitation at 806 nm, the nanoparticles exhibit emission in the first and second biological optical transparency windows. The temperature sensing properties were evaluated from the luminescence intensity ratio of the thermally coupled emission lines corresponding to the R 1, R 2 → Z 5 transitions between the Stark sublevels of the 4 F3/2 and 4 I9/2 electronic states of Nd 3+ in the physiological temperature range of 20–50 °C. GSAG:Nd 3+ nanoparticles exhibit a maximal relative thermal sensitivity of 0.20% °C −1, higher than that of YAG:Nd 3+ nanoparticles used as a control, due to the difference in the crystal field of the host matrices. A higher synthesis temperature in the range of 300–400 °C was also provided to improve the crystallinity of the GSAG:Nd 3+ nanoparticles which results in a higher relative thermal sensitivity. Our results demonstrate the potential of GSAG:Nd 3+ nanoparticles as luminescence nanothermometers and emphasize the interest of the GSAG matrix itself, which with the presence of Gd, could lead to multimodal diagnostic applications in nanothermometry and magnetic resonance imaging (MRI).